Natural Products of Plants and Animal Origin Improve Albumen Quality of Chicken Eggs - Obianwuna, Uchechukwu Edna; Oleforuh-Okoleh, Vivian U.; Wang, Jing; Zhang, Hai-Jun; Qi, Guang-Hai; Qiu, Kai; Wu, Shu-Geng (Frontiers in Nutrition, 2022)
Albumen quality is recognised as one of the major yardsticks in measuring egg quality. The elasticity of thick albumen, a strong bond in the ovomucin-lysozyme complex, and excellent biological properties are indicators of high-quality albumen. The albumen quality prior to egg storage contribute to enhance egg's shelf life and economic value. Evidence suggests that albumen quality can deteriorate due to changes in albumen structure, such as the degradation of β-ovomucin subunit and O-glyosidic bonds, the collapse of the ovomucin-lysozyme complex, and a decrease in albumen protein-protein interaction. Using organic minerals, natural plants and animal products with antioxidant and antimicrobial properties, high biological value, no residue effect and toxicity risk could improve albumen quality. These natural products (e.g., tea polyphenols, marigold extract, magnolol, essential oils, Upro (small peptide), yeast cell wall, Bacillus species, a purified amino acid from animal blood, and pumpkin seed meal) are bio-fortified into eggs, thus enhancing the biological and technological function of the albumen. Multiple strategies to meeting laying hens’ metabolic requirements and improvement in albumen quality are described in this review, including the use of amino acids, vitamins, minerals, essential oils, prebiotics, probiotics, organic trace elements, and phytogenic as feed additives. From this analysis, natural products can improve animal health and consequently albumen quality. Future research should focus on effects of these natural products in extending shelf life of the albumen during storage and at different storage conditions. Research in that direction may provide insight into albumen quality and its biological value in fresh and stored eggs.